METHODS OF TREATMENT OF SYMPTOMATIC UTERINE FIBROIDS THROUGH THE PRISM OF TIME (REVIEW OF SCIENTIFIC LITERATURE) - Марина Алексеевна Тимченко; Юрий Сергеевич Оловянников; Мария Геннадьевна Николаева (The Publishing House Medicine and Enlightenment, 2023)
The review article presents the results of the published works, concerning the studies of therapy of symptomatic uterine fibroids. As known, uterine fibroids takes the second place in the structure of gynecological pathology without downtrend. Conducted investigations demonstrate ambiguous results in the use of surgical and minimal invasive methods of treatment. Part of the authors lean toward the election of myomectomy as a method with the minimal influence on fertility and excluding the disease recurrence. The group of investigators, adherents of more sparing approaches to the organ-preserving tactics substantiate and prove the expediency of making the embolization of uterine arteries, taking into consideration the individual approach and risk assessment of long-term results. Discussability of the questions of choosing the methods of treatment of symptomatic uterine fibroids, taking into the consideration a long-term exodus and perspective of the realization the reproductive function determine the necessity of conducting further perspective investigations.